PENATAAN ADMINISTRASI PENDUDUK PINDAH DATANG DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA JAMBI PROVINSI JAMBI - Burhanuddin Dalil; Nurmaidah Sitanggang (PRODI ADMINISTRASI PEMERINTAHAN DAERAH FAKULTAS MANAJEMEN PEMERINTAHAN IPDN, 2019)
This research method uses descriptive qualitative method with an inductive approach. The data used are primary and secondary data obtained by data collection techniques namely observation, interviews, and documentation. The data analysis technique used by the author is by reducing data, presenting data, and drawing conclusions. The results of the study based on the analysis and observations made by the author while doing an internship in the field can be seen that the implementation of the administration of the population moved to the Department of Population and Jambi City Civil Registration in accordance with existing procedures, many people who were satisfied given, although in the implementation of administrative arrangements the population moved in there were still some obstacles including the lack of employees in the moving services section so that it could slow down the administrative process, inadequate room facilities for storing all the files in an irregular stack, lack of public awareness the importance of the certificate of transfer to come. Based on research observations the authors suggest that the Department of Population and Civil Registration do add employees in the area of ​​Moving Come services, add facilities and infrastructure to run the process in an orderly and organized manner, and socialize the importance of the procedure and the procedure for moving letters. Keywords: Arrangement, Moving Mail